Solitary fibrous tumor of the pleura: biphasic contrast-enhanced CT findings with emphasis on differential diagnosis - Ying Xiao; Jiaer Chen; Sen Jiang; Ruowei Chen; Yangkang Li (Frontiers in Medicine)
ObjectiveSolitary fibrous tumor of the pleura (SFTP) is a rare neoplasm. Familiarity of its radiologic features may allow preoperative diagnosis and improve management of patients. However, radiological studies on the comparison of imaging findings between SFTP and other thoracic tumors are scarce. This study aims to evaluate the radiologic features of SFTP on biphasic contrast-enhanced computed tomography (CT) images with focus on the differential diagnosis.MethodsThe clinical data and CT images of 25 patients with pathologically proven SFTP and 42 patients with other types of thoracic tumors were retrospectively reviewed. Patient age, CT features including lesion size, shape, margin, precontrast density, intratumoral calcification, intratumoral vessel, enhancement degree, and blood supply were evaluated. Qualitative data were compared with Chi-square test and quantitative data were compared with t-test. When the radiologic features appeared to be significant in the univariate analysis, multivariate analysis was performed for SFTP group using logistic regression model. The diagnostic performance was established using the area under the receiver operating characteristic (ROC) curve.ResultsFive CT features, including tumor size, contour, intratumoral vessels, marked enhancement, and blood supply from pulmonary circulation of two groups differed significantly (P < 0.05). Moreover, blood supply from pulmonary circulation was identified as the independent signs of SFTP by multivariate logistic regression analysis. The area under the ROC curve was 0.744 (P < 0.05).ConclusionSolitary fibrous tumors of the pleura are often seen as large, well circumscribed masses with intense heterogeneous enhancement and multiple intratumoral vessels on CT images. For large tumors which are difficult to identify, carefully looking for the feeding artery from pulmonary circulation will be helpful to diagnose SFTP.